Iron-Catalyzed P(O)–S Bond Formation through Cross-Dehydrogenative Coupling of Thiols with P(O)H Compounds - Ji, Yuge; Han, Bing; Liu, Hongbin; Song, Di; Liu, Lei; Wang, Gang (Synthesis, 2025)
We herein report an iron(salan)-catalyzed cross-dehydrogenative coupling of thiols with P(O)H compounds for the efficient synthesis of a range of thiophosphates, thiophosphinates, and thiophosphinites. This mild and practical method employs environmentally benign air as terminal oxidant, and earth-abundant metal iron at a low loading as catalyst, and exhibits broad substrate scope and good functional group tolerance, which is applicable to bioactive molecule preparation.
Keywords: iron catalysis; P(O)–S bond formation; cross-dehydrogenative coupling; thiophosphates; synthetic methods